2000
DOI: 10.1152/jappl.2000.89.5.1991
|View full text |Cite
|
Sign up to set email alerts
|

Faster top running speeds are achieved with greater ground forces not more rapid leg movements

Abstract: We twice tested the hypothesis that top running speeds are determined by the amount of force applied to the ground rather than how rapidly limbs are repositioned in the air. First, we compared the mechanics of 33 subjects of different sprinting abilities running at their top speeds on a level treadmill. Second, we compared the mechanics of declined (-6 degrees ) and inclined (+9 degrees ) top-speed treadmill running in five subjects. For both tests, we used a treadmill-mounted force plate to measure the time b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
645
10
16

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 732 publications
(728 citation statements)
references
References 27 publications
57
645
10
16
Order By: Relevance
“…The constant L stance assumption is broadly supported by a range of empirical data (Cavagna et al 1976;Greene & McMahon 1979;Greene 1985;Weyand et al 2000). Our model deviates subtly from that of Greene (1985) in that we assume protraction time-the time taken to swing the leg forwards (t swing ) between each stance period for that leg-to be constant, rather than assuming a constant stride frequency.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The constant L stance assumption is broadly supported by a range of empirical data (Cavagna et al 1976;Greene & McMahon 1979;Greene 1985;Weyand et al 2000). Our model deviates subtly from that of Greene (1985) in that we assume protraction time-the time taken to swing the leg forwards (t swing ) between each stance period for that leg-to be constant, rather than assuming a constant stride frequency.…”
Section: Introductionmentioning
confidence: 85%
“…The kinematic parameters are derived from observations reported by Weyand et al (2000), in which the relevant values are shown to be remarkably consistent and independent of sprint performance, at least within each gender. We, therefore, use t swing Z 0.315 s for male and female, and L stance Z0.99 m (male) or 0.90 m (female).…”
Section: þmentioning
confidence: 99%
See 1 more Smart Citation
“…Within many sporting activities, techniques that maximise performance cause larger forces and loading rates (Weyand et al, 2000) to be exerted on the body, potentially increasing the likelihood of injury (in the context of fast bowling, maximising performance can be considered as delivering the ball as fast as possible in the desired direction). In cricket fast bowling it has been suggested that bowlers who release the ball at faster speeds experience higher peak ground reaction forces and loading rates (Portus et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that "over speed" training or fast velocity running is beneficial for improving cardiovascular and neuromuscular function [21]. It has been demonstrated that this type of training is effective at producing greater rates of muscular force generation [22,23]. Traditional "over speed" training must be approached cautiously because of increased peak ground reaction forces that accompany running at fast velocity.…”
Section: Unloaded Treadmillsmentioning
confidence: 99%